Some Positive Trends in the Development of University Science in Russia at the Present Time - L. V. Konstantinova; E. S. Titova; A. M. Petrov; D. A. Shtykhno (Высшее образование в России)
The development of university science is one of the state policy priorities in Russia today. To determine this process prospects, it is important to identify positive trends and best practices of leading Russian universities scientific activity. For this purpose, the article considers the organizational features and sources of university science funding, analyzes the main indicators of research performance and practices of research policy implementation, summarizes the scientific achievements of leading Russian universities. The article uses the methods of universities monitoring activities statistical analysis and substantive analysis of information about the universities` scientific activities posted in open sources. The conclusions are drawn about the formation in Russia leading universities group with a stable priority of research activities, the core of which is formed by leading technical sectoral universities and regional polytechnic universities, the practices of science organization and the main scientific achievements of which can significantly influence the further development of domestic university science, as well as the world scientific knowledge expansion and Russian society socio-economic development issues solution.